Bronchial artery embolization for hemoptysis in adult patients with cystic fibrosis: a single-center retrospective study. (April 2023) - Roussel, Alexandre; Sage, Edouard; Roux, Antoine; Guth, Axel; Mellot, François; Gravel, Guillaume
Background: Hemoptysis is a severe complication of cystic fibrosis (CF) for which bronchial artery embolization (BAE) is an efficient primary therapeutic option. However, recurrence is more frequent than for other etiologies of hemoptysis. Purpose: To assess the safety and efficacy of BAE in patients with CF and hemoptysis and predictive factors for recurrent hemoptysis Material and Methods: This retrospective study reviewed all adult patients with CF treated by BAE for hemoptysis in our center from 2004 to 2021. The primary endpoint was the recurrence of hemoptysis after bronchial artery embolization. Secondary endpoints were overall survival and complications. We introduced the vascular burden (VB) defined as the sum of all bronchial artery diameters measured on pre-procedural enhanced computed tomography (CT) scans. Results: A total of 48 BAE were performed in 31 patients. A total of 19 recurrences occurred with a median recurrence-free survival of 3.9 years. In univariate analyzes, percentage of unembolized VB (%UVB) (hazard ratio [HR] = 1.034, 95% confidence interval [CI=1.016–1.052; P  < 0.001) and %UVB vascularizing the suspected bleeding lung (%UVB-lat) (HR = 1.024, 95% CI=1.012–1.037; P  < 0.001) were associated with recurrence. In multivariate analyzes, only %UVB-lat remained significantly associated with recurrence (HR = 1.020, 95% CI=1.002–1.038; P  = 0.030). One patient died during follow-up. No complication of grade 3 or higher was reported according to the CIRSE classification system for complications. Conclusion: When possible, unilateral BAE seems sufficient in patients with CF with hemoptysis even in such a diffuse disease involving both lungs. The efficiency of BAE could be improved by thoroughly targeting all arteries vascularizing the bleeding lung.